2008
DOI: 10.1152/ajplung.00027.2008
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression in the developing diaphragm: significance for congenital diaphragmatic hernia

Abstract: Clugston RD, Zhang W, Greer JJ. Gene expression in the developing diaphragm: significance for congenital diaphragmatic hernia. Am J Physiol Lung Cell Mol Physiol 294: L665-L675, 2008. First published February 8, 2008 doi:10.1152/ajplung.00027.2008.-Congenital diaphragmatic hernia (CDH) is a frequently occurring birth defect and a source of potentially fatal neonatal respiratory distress. Recently, through the application of detailed karyotyping methods, several CDH-critical regions within the human genome hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 67 publications
(92 reference statements)
6
59
1
Order By: Relevance
“…They concluded that the 15q26 critical region contains a cluster of genes, such as MEF2A, NR2F2, and CHD2, that are expressed in rodent diaphragm development, thus supporting other reports that deletions in this region are associated with CDH [8].…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…They concluded that the 15q26 critical region contains a cluster of genes, such as MEF2A, NR2F2, and CHD2, that are expressed in rodent diaphragm development, thus supporting other reports that deletions in this region are associated with CDH [8].…”
Section: Discussionsupporting
confidence: 70%
“…Clugston et al [8] used rodent diaphragms to study the expression of CDH candidate genes from 15q26, as well as FOG2 and GATA4, two genes in other CDH critical regions at 8q22-q23 and 8p23.1, respectively [8]. They concluded that the 15q26 critical region contains a cluster of genes, such as MEF2A, NR2F2, and CHD2, that are expressed in rodent diaphragm development, thus supporting other reports that deletions in this region are associated with CDH [8].…”
Section: Discussionmentioning
confidence: 81%
“…1 I and J). To determine the cell type that contributes to the diaphragmatic tissue overgrowth, we examined the expression of myosin heavy chain (MyHC) and Wilms tumor-1 (Wt1) in sections of Kif7 dd/dd embryos; MyHC labels diaphragmatic skeletal muscle, and Wt1 is expressed in the early mesothelium and throughout the nonmuscle mesenchymal cells of the diaphragm (24,25). We determined that the skeletal muscle fiber distribution and orientation were normal at E13.5, whereas the nonmuscular Wt1 + cells accumulated throughout the mutant diaphragms ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In animal models, a CDH-like phenotype has been linked to a deficient maternal intake of vitamin A (Anderson, 1941), teratogenic disturbances of retinoid homeostasis (Mey et al, 2003), genetic defects in retinoid signaling (Mendelsohn et al, 1994), and the expression of retinoid-related genes in the primordial diaphragm (Clugston et al, 2008). Noteworthy, administration of vitamin A reduced the incidence of CDH in animal models (Thébaud et al, 1999).…”
Section: Introductionmentioning
confidence: 99%